P–T-t conditions of successive deformation stages during exhumation of orogenically thickened crust; a case study from the Aar Massif, Central Alps, Switzerland - Edwin Gnos; Josef Mullis; Christian A. Bergemann; Thomas Pettke; Emmanuelle Ricchi; Axel. K. Schmitt (Swiss Journal of Geosciences)
Abstract Obtaining precise pressure–temperature-time constraints on the history of exhumation of orogenically thickened crust using rock-forming minerals of greenschist-facies rocks can be a challenging task. Rare examples exist where structurally distinct hydrothermal mineralisations have been used to pin-point specific stages during this evolution. This study combines hydrothermal fissure-quartz fluid and solid inclusion data with Ti-in-quartz thermometry, solute thermometry, and fissure monazite-(Ce) Th-Pb ion probe dating in order to establish a link between hydrothermal mineral crystallisation and major faulting events in the Grimsel Pass study area, central Aar Massif, Switzerland. Six fluid inclusion populations in quartz are distinguished in the older, steeply NNW-dipping fissure at the well-known Zinggenstock locality, four can be identified in quartz in younger, vertical fissures. All data together constrain formation and subsequent stepwise growth and evolution of the fissures to a P–T-t range of 450 °C/440 MPa and 300 °C/240 MPa between c. 15 and 7 Ma. In quartz zones containing rutile-whiskers in fluid inclusions, Ti-in-Qtz thermometry yields temperatures comparable to fluid inclusion solute thermometry. The combined data indicate that the oldest cleft quartz generation formed c.15 Ma ago during reverse faulting at 450 °C/440 MPa. A major change in the direction of the regional stress field linked with onset of dextral strike-slip movements along the Rhone-Simplon-Centovalli fault system then led to predominant dextral strike-slip faulting starting at c. 12–11 Ma, at P–T conditions between 375 °C/320 MPa and 330 °C/230 MPa. At Zinggenstock, the original cleft becomes overprinted by sinistral shear zones, and fluid advection at 330 °C/230 MPa. This CO2-bearing fluid led at the Zinggenstock location to the formation of white mica (muscovite-ferriphengite) at the expense of chlorite. At Oberaar, renewed dextral strike-slip reactivation occurred between c. 10 and at 7 Ma at conditions of 330 °C/230 MPa to 300 °C/240 MPa. Our data document variable stress regimes, locally associated with focused fluid flow, across an approximate depth interval of 16.3–8.5 km (~ 440 to 230 °C) during unroofing of the orogenically thickened crust. Hydrothermal mineral formation ages precisely constrain the chronology of successive deformation events, thus offering valuable constraints for unravelling the mechanisms of tectonically and buoyancy-driven exhumation of peripheral domains of the NW European Alps. Together, these data permit to estimate exhumation and cooling rates independent of thermochronology.